Implementasi Pengembangan Infografis Terintegrasi sebagai Media dan Suplemen Pembelajaran Bahasa Inggris di Sekolah Dasar - Ana Anggi Anggraini; Erwin Rahayu Saputra (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2023)
Learning English requires innovation as a form of learning adaptation to the current changing times, namely the adaptation period for new habits after the Covid-19 intervention. One form of learning innovation is through the development of learning media. The focus of this research is to describe the implementation of integrated infographic learning media with learning videos resulting from the design and development of researchers for learning English in elementary schools. The narrative inquiry method with a qualitative approach is the basis used for this research. Data collection techniques through interviews, observation and assisted by literature study. Learning English is carried out in class IV at SDN Ceungceum, Tasikmalaya Regency by applying a scientific learning model utilizing integrated infographic learning media with the advantage of helping to understand the concept of Types of Energy Sources as well as being used as an addition and extension of insight after learning. The integrated infographic media is designed by adding a QR code and a connected link to learning videos. The response of the students was very enthusiastic during the learning process. Learning outcomes are shown by discussion activities, presentations, and tests to make sentences get very good results